Lifestyle patterns as predictors of drowsy driving in Greece - Τζαμαλούκα Γ.; Χρηστάκης Ν.; Παπαδακάκη Μ.; Γναρδέλλης Χ.; Δαρβίρη Χ.; Χλιαουτάκης Ι. (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF